Metode Hermeneutika Kesadaran (Fenomenologi) dalam Memahami Teks - Muhammad Adlan Nawawi (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2017)
The Qur’an is a living text that interact to the horizons that surround it. The existence of the subject as a reader and interpreter produces various ways and outputs of understanding. Subjects speak- ing with the text within the scope of the two interacting are a form of phenomenological activity. Subjects perceive text as a sign pointing to diverse realities. In the study of phenomenology, the phenomenon is not veiled by the curtain of reality resulting from the perception of the subject. Thus, the meanings of the text are not born in a vacuum, but always involve the consciousness of the subject. This shows that the development of understanding and methodology in understand- ing the Qur’an (text) is a necessity. The text’s horizon will always be in contraction with the subject’s horizon based on the consciousness that grows in the period of time and age.